2015
DOI: 10.1186/s13104-015-1463-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of full-text publication and publishing predictors of abstracts presented at an Italian public health meeting (2005–2007)

Abstract: BackgroundIn Public Health, a thorough review of abstract quality evaluations and the publication history of studies presented at scientific meetings has never been conducted. To analyse the long-term outcome of quality abstracts submitted to conferences of Italian Society of Hygiene and Public Health (SItI) from 2005 to 2007, we conducted a second analysis of previously published material aiming to estimate full-text publication rate of high quality abstract presented at Italian public health meetings, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
4
0
2
Order By: Relevance
“…Our findings give scientific corroboration to the common perception among research funders and institutions that conferences play a significant role in disseminating and improving academic work. These results are consistent with correlations found in previous empirical work (Winnik et al, 2012, Castaldi et al, 2015, and Chai and Freeman, 2017, but-to the best of our knowledge-this study is the first to have used quasi-experimental evidence to estimate the benefits of conferences and in this sense is wholly novel within the existing literature. 4 More broadly, we contribute to a growing body of work that investigates the impacts of face-to-face interactions and the determinants of knowledge flow.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings give scientific corroboration to the common perception among research funders and institutions that conferences play a significant role in disseminating and improving academic work. These results are consistent with correlations found in previous empirical work (Winnik et al, 2012, Castaldi et al, 2015, and Chai and Freeman, 2017, but-to the best of our knowledge-this study is the first to have used quasi-experimental evidence to estimate the benefits of conferences and in this sense is wholly novel within the existing literature. 4 More broadly, we contribute to a growing body of work that investigates the impacts of face-to-face interactions and the determinants of knowledge flow.…”
Section: Introductionsupporting
confidence: 92%
“…See Merton (1968), Salganik et al (2006), Azoulay et al (2013. 4 Winnik et al (2012) and Castaldi et al (2015) compare "accepted" vs. "rejected" papers, so a selection effect (the extent to which the conference committee selects for papers that are likely to have greater impact) is likely to be a confounder to any conference effect. Chai and Freeman (2017) conduct a more controlled analysis, by comparing patterns of collaboration and citations among attendees of the Gordon Research Conferences with patterns among a matched group of non-conference attendees, and instrumenting conference attendance by individuals' distance to the conference.…”
Section: Tablementioning
confidence: 99%
“…Consistent with a recent study [ 14 ], our study showed that a larger sample size (n ≥ 100) was significantly associated with more frequent publication. However, given that prior studies have shown conflicting results for the effect of sample size on the likelihood of publication [ 1 , 4 , 20 ], further studies are needed to evaluate this association.…”
Section: Main Textmentioning
confidence: 99%
“…However, our results on research affiliated institutions are not consistent with other studies. Castaldi et al 19 concluded first authors affiliated with university hospitals were more likely to achieve FTP than non-university hospitals (P=0.001). Winnik et al 25 also identified a significant association with university hospital affiliated institutions and the likelihood of FTP (OR=1.53; P=0.03).…”
Section: Discussionmentioning
confidence: 99%